Egypt : Teachers - World Bank (Washington, DC, 2014)
In 2008 (the most recent data available), Egypt spent 3.8 percent of Gross Domestic Product, or GDP on public education; in 2003 this figure was recorded as 4.9 percent. In 2008, Egypt spent 11.9 percent of total public spending on education; in 2003, this figure was recorded as 16.2 percent. However, over recent years, Egypt has achieved important improvements in access to primary education. The primary enrollment rate reached 94 percent (2007) from 86 percent at the beginning of the decade. Egypt's secondary enrollment rate (71 percent in 2002) compares favorably to other countries in the Middle East and North Africa region and to other low-middle income countries. Despite these improvements, learning outcomes remain a source of concern. Egyptian students mean scores in the Trends in International Mathematics and Science Study Mathematics (TIMSS) declined between 2003 and 2007, from 406 to 391 points. Thus, improving the quality of education is a priority for the country.